2015
DOI: 10.15296/ijwhr.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Post-dural Puncture Headache in the Obstetric Patient: Needle Size, Number of Dural Puncture and Timing of Ambulation

Abstract: Objectives: This prospective study compared the incidence of post-dural puncture headache (PDPH) in obstetric patients undergoing spinal anesthesia for caesarean section from April 2012 to April 2013 in one year. We also evaluated the relationship between needle size, number of dural punctures, timing of ambulation and PDPH after cesarean section. Materials and Methods: A total of 319 American Society of Anesthesiologists (ASA) I-II full term pregnant women, scheduled for caesarean section under spinal anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…20 Present findings are in congruence with that of Rasooli S et al whose observations again linked the occurrence of PDPH with multiple attempts at subarachnoid block.…”
Section: Discussionsupporting
confidence: 93%
“…20 Present findings are in congruence with that of Rasooli S et al whose observations again linked the occurrence of PDPH with multiple attempts at subarachnoid block.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, 85/391 obstetric mothers (21.7%) develop PDPH. This finding is relatively higher as compared to studies conducted by Abdullayev et al, 17 Rasooli et al, 18 and Shaikh JM et al, 19 which report the prevalence of PDPH as 9%, 1.9%, and 4.8% respectively. We concluded that, the higher prevalence of PDPH in our study is contributed by wide spread utilization of large bore and quincke type spinal needle (18G, 20G & 23G) as compared to the previous studies which used fine quincke type as well as a traumatic needle spinal needle.…”
Section: Descriptioncontrasting
confidence: 58%
“…However, some other studies 17,26,27 failed to demonstrate a statistically significant deference in the incidence of PDPH between 26-G cutting spinal needle and 26-G a traumatic spinal needle, 25-G Quincke spinal needle and 27-G Quincke spinal needle, and 25-G quincke needle versus 27-G quincke needle versus 27-G whitacre needle, respectively. From these findings, we recognize that, the needle design become more determinant for the development of PDPH than gauges of the spinal needle as the gauges of the spinal needle become smaller (≤ 25 G) In addition, our study also found a statistically significant relation between the numbers of spinal attempt and PDPH.…”
Section: Descriptionmentioning
confidence: 96%
“…[ 16 ] The PDPH incidence reported by Rasooli et al [ 17 ] who used a 27G Quincke needle, was high compared with other studies. [ 16 17 18 ] We used a 27G Quincke spinal needle and found a PDPH incidence of 8.2% in parturient women. One of the reasons for the different incidences found in parturient women may be the SA technique; inserting the needle parallel to the dura fibers is proposed to reduce PDPH incidence.…”
Section: Discussionmentioning
confidence: 99%